Child tracing: locating the paternal homes of "children born of war". Issue 5 (3rd July 2020) - Mutsonziwa, Tinashe B. C.; Anyeko, Ketty; Baines, Erin
ABSTRACT: During the war in northern Uganda, thousands of women abducted as girls by the rebel group, the Lord's Resistance Army, were released and escaped to return home, many with children born as the result of "forced marriage". Most women and children no longer have contact with their children's father by choice, because they are dead, or their identity is unknown. However, in some cases, mothers seek to identify and unite their children with their paternal clan. We consider the process of child tracing, present some of the reasons driving it, the diversity of cases involved and the challenges faced.